SOCIAL CRITIQUE IN GABRIEL GARCIA MARQUEZ’S "ONE HUNDRED YEARS OF SOLITUDE" - Satrih Satrih (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
The development of nations can be measured from the kind of readings and the level of appreciation of their societies towards science, art, and literature. Hence, the researcher conducted research on social critique in Gabriel Garcia Marquez’s novel One Hundred Years of Solitude to give a description of the social critique revealed in the novel. The research used a sociological approach known as Marxist criticism, which relates to theories of class conﬂict supported by the social background of Colombian society. It answers the research question, what are the social critiques submitted by Gabriel Garcia Marquez in his novel One Hundred Years of Solitude? The research data was taken from the text of the novel in its English version published in 1995, London by David Campbell Publisher. Two techniques of data analysis were done; descriptive analysis. The researcher found that the story of One Hundred Years of Solitude contains a Marxist critique of; State, the existence of the state with all its instruments (the army, magistracy, etc.) by which the class in power suppresses another or other classes have plundered the innocent and peaceful Macondo without a state; Religion, as an ideologist religion, conservatism is regarded as a static force marked with hypocrisy and inconsistency, leading to destruction; and Capitalism, marked by modern technology along with a moral and spiritual decline, and proud capitalists for their high social status oppressing the lower class (laborers) eventually turns progress to brutality